Ethnobotanic Study of Use of Medicinal Plants Utilized in the Quilombola Community of Chapada Da Natividade, Tocantins, Brazil - Cardoso, Vanilza Dias; Mourão, Dalmarcia de Souza Carlos; Haesbaert, Fernando Machado; Ferreira, Talita Pereira de Souza; Osorio, Pedro Raymundo Argüelles; Souza, Rosângela Ribeiro de; Costa, Priscila Fonseca; Ferreira, Eduardo Côrtes Ribeiro; Aguiar, Raimundo Wagner de Souza; Santos, Gil Rodrigues dos (Journal of Diseases, 2018)
The knowledge of medicinal plants utilized by the quilombolas is considered important in the conservation of these plants within the Brazilian biodiversity, and must be preserved and transmitted over the generations. Thus, the objective of this study was to make a survey of the use of medicinal plants utilized by the Quilombola Community of Chapada da Natividade, located in the state of Tocantins, Brazil. The data gathering was carried through informal interviews with listing of the plants and the sampling technique utilized for selection of informers was the “Snow Ball”. There were registered 32 species belonging to 22 distinct families. The families with the higher number of cited species were Fabaceae, Anacardidaceae and Lamiaceae. The predominant medicinal uses are mostly associated to the respiratory and tegumental systems, with the leaves being the most used parts, in teas by decoction and infusion. Also, there was carried the study of the main illnesses, considering the use of medicinal plants for the treatment of them. The results show a vast diversity of vegetal species utilized, and that the role of the medicinal plants is not only as agent in the cure of diseases, but also as cultural form.